Using a Theatre as Representation Scenario as a Teaching Vehicle in B.Ed and M.Ed Preparation Programs (LEARNing Landscapes, 2008)
The following article demonstrates the use of the dramatic scenario, The Insurrection (a TAR/ethno-drama fiction work) to teach fundamental educational administration concepts to graduate and preservice teacher candidates. The scenario was written specifically to address the conflicts related to communication within a secondary school community and is used as a provocation tool in classroom discussions.
Keywords: educational administration; theatre; scenario; secondary school; conflict; communication; TAR/ethno-drama fiction